+0  
 
0
44
2
avatar

Another Algebra 2 question...

Guest Oct 3, 2017
Sort: 

2+0 Answers

 #1
avatar
0

Solve for x:
(3 x - 2)^2 = (5 x + 1)^2

Take the square root of both sides:
3 x - 2 = 5 x + 1 or 3 x - 2 = -5 x - 1

Subtract 5 x - 2 from both sides:
-2 x = 3 or 3 x - 2 = -5 x - 1

Divide both sides by -2:
x = -3/2 or 3 x - 2 = -5 x - 1

Add 5 x + 2 to both sides:
x = -3/2 or 8 x = 1

Divide both sides by 8:
x = -3/2         or          x = 1/8

Guest Oct 3, 2017
 #2
avatar+26277 
+3

"Use the identity a2-b2=(a-b)(a+b) to solve the problem:  (3x-2)2=(5x+1)2"

 

Rewrite as:  (5x+1)2 - (3x-2)2 = 0

 

Let a = 5x+1 and b = 3x-2

 

(5x+1)2 - (3x-2)2 → (5x+1 - (3x-2))(5x+1 + 3x-2) → (2x + 3)(8x - 1)

 

so (2x + 3)(8x - 1) = 0

 

Hence 2x + 3 = 0   giving  x = -3/2

 

or  8x - 1 = 0  giving  x = 1/8

.

Alan  Oct 3, 2017

17 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details